Beyond Mastery: Evaluating Students’ English Writing Achievement Based on Minimum Mastery Criteria in an Islamic Elementary School - Nelly Khoirina; Widhiyanto Widhiyanto (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2026)
This study evaluates students’ English writing achievement based on Minimum Mastery Criteria (Kriteria Ketuntasan Minimal/KKM) in an Indonesian Islamic elementary school. The study addresses the need to critically examine whether students’ attainment of mastery criteria reflects actual writing competence among young learners. Employing a quantitative descriptive evaluation design, the study involved 22 second-grade students whose writing scores were collected through classroom-based assessment records. Data were analyzed using descriptive statistical techniques, including mean score calculation, score distribution analysis, and mastery percentage evaluation. The findings reveal that all students achieved the Minimum Mastery Criteria of 75, resulting in a 100% mastery rate with a mean score of 87.36. However, further analysis demonstrates variation in achievement levels, with students distributed across minimum, moderate, and high achievement categories. These findings indicate that although all students met the established mastery threshold, writing competence remained differentiated across learners. The study concludes that KKM-based evaluation is useful for measuring baseline achievement but should not be interpreted as a comprehensive indicator of writing proficiency. Therefore, teachers are encouraged to complement mastery-based assessment with broader evaluation approaches to capture more complex dimensions of students’ writing development.